ANALISIS BUTIR SOAL ULANGAN AKHIR SEMESTER PPKn KELAS X SMAN 2 MEMPAWAH TAHUN AJARAN 2018/2019 - Wahyuni, Fitri; Rosyid, Rum; Rahmatika, Ika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aims to determine the quality of Civic Education Multiple-Choice items of the first semester final test of tenth-grade students of SMA Negeri 2 MempawahHilirin the academic year of 2018/2019 based on the difficulties, differentiation, validity,reliability, and the effectiveness of distractors.This research used a descriptive quantitative method. The research samplewas taken randomly,comprising 67 tenth-grade students.The object was the first-semester final test items,answer keys, and students’answer sheets. The technique of data collection was done through the interview and documentation method. The analyze dataused the ITEMAN version 3,00. The results show 17 hard questions items (42.5%), 16 medium items (40%), and seven easy items (17.5%). Based on the ability of the differentiating question, there are 10 items categorized as poor items (25%), 24 fine items (60%), and 6 good items (15%). Based on validity,there are 20 valid items (50%), and 20 invalid items (50%). Based on reliability,the test items are reliable with a fine category by the alpha value of 0.548. Based on the effectiveness of distractor,there are 21 excellent items (52.5%), 10 good items (25%), seven fine items (17.5%), and two poor items of distractor (5%). Therefore,the test items of the first-semester final test have good quality.Keywords: Test Item Analysis,Civic Education, SMA Negeri 2 MempawahHilir.